Does Exchange-Rate Stability Increase Trade and Welfare? - Bacchetta, Philippe; van Wincoop, Eric (American Economic Review, 2000)
This paper develops a simple general-equilibrium framework to study the effect of the exchange-rate system on trade and welfare. An important feature of the model is deviations from purchasing-power parity, caused by rigid price setting in buyers' currency. In a benchmark model with separable preferences and only monetary shocks, trade is unaffected by the exchange-rate system, consistent with most evidence. In general, both trade and welfare can be higher under either exchange-rate system, depending on preferences and on the monetary-policy rules followed under each system. There is no one-to-one relationship between the levels of trade and welfare across exchange-rate systems. (JEL F31, F33, F41)